Fundamentals of Entrepreneurship (ENT300) : Kenyalang Herbal Spa / Raden Siti Ayu Radin Amin Othman ... [et al.] - Radin Amin Othman, Raden Siti Ayu; Shamsul Azhar, Nurshafiqa; Mazaruddin, Nurashikin; Alexander, Christina (2012)
Our company name is Kenyalang Herbal Spa. The business has been decided on the form of partnership. Each of partners contributes certain amount of capital as agreed in contract. The major business activity is giving special services such as body and feet massage to all level of ages of women including kids. Each of the partners is entitled to participate in the business management and there are no sleeping partners. We have all agreed that RADEN SlTl AYU BINTI RADIN AMIN OTHMAN to hold position as a General Manager as well as Administration Executive, NUR SHAFIQA BINTI SHAMSUL AZHAR as a Marketing Executive, NORASIKIN BINTI MAZARUDDIN as an Operational Executive and CHRISTINA MUTI A/K ALEXANDER as a Financial Executive. The appointment of the General Manager is based on agreement among all the partners and also concerning about the experience, skills and ability owned by the general manager. The management team will be led by the general manager and assist by the other executives. The general manager will be responsible in planning, leading, controlling and organizing the business. The administration executive is responsible for the job that related to administration such as planning and organizing the remuneration schedule salary and wages. The operational executive is responsible to the entire job that related to the operation and will monitor and coordinate the operation for the business. The marketing executive will be responsible for creating the market, market size and forecasting the future market. Lastly, the financial executive will handle the financial matters such as preparing the budget and financial statement for expenses of each department and controlling the flow of the money of the organization.